The influence of entrepreneurial training on innovativeness / Siti Nur Adilah Kamarudin and Nur Jalilah Yahaya - Kamarudin, Siti Nur Adilah; Yahaya, Nur Jalilah (2013)
This research was conducted for the purpose of “The Influence of Entrepreneurial Training on Innovation”. The main objective of this research was to identify the level of innovativeness and the relationship between entrepreneurial training and innovativeness. The respondent of this study was from Tunas Mekar Kelantan participants. A questionnaire had been distributed to those who involve in Tunas Mekar program which is 68 participants. The data was obtained from primary data by using questionnaire. There have three section in the questionnaire consist of Section A for demographic profile, Section B for independent variables which are Risk Propensity, Creativity/innovation, Opportunity Identification and Role Model. While Section C consists of dependent variable this is innovativeness. The researcher analyze the data by using SPSS 21 in order to identify the mean, median, standard deviation, reliability test, correlation testing and regression analysis. At the end of the result, the researcher found that there are two hypotheses that are supported which are creativity/innovation and role model.